2020
DOI: 10.1007/s00402-020-03599-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after nonoperatively treated non-displaced Lisfranc injury: a retrospective case series of 55 patients

Abstract: Background Current knowledge of the role of the nonoperative treatment of Lisfranc injuries is based on a few retrospective case series. Hence, consensus on which patients can be treated nonoperatively does not exist. The aim of this study was to investigate outcomes after nonoperative treatment of Lisfranc injuries. Methods In this study, patients were collected by recruiting all computer tomography-confirmed Lisfranc injuries treated during a 5-year period at a major trauma hospital. Between 2 and 6 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Similarly Choi et al reported that overall AOFAS score of patients who underwent open reduction and internal fixation for SLI was 85.7 [6]. On the other hand, Ponkilainen et al investigated 55 patients with < 2 mm of C1M2 avulsion in NWB CT who were treated nonoperatively [26]. Overall patient-reported outcome measure with visual analog scale foot and ankle was over 90 points in 64% and over 80 points in 78% of them.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly Choi et al reported that overall AOFAS score of patients who underwent open reduction and internal fixation for SLI was 85.7 [6]. On the other hand, Ponkilainen et al investigated 55 patients with < 2 mm of C1M2 avulsion in NWB CT who were treated nonoperatively [26]. Overall patient-reported outcome measure with visual analog scale foot and ankle was over 90 points in 64% and over 80 points in 78% of them.…”
Section: Discussionmentioning
confidence: 98%
“…15 High-energy mechanisms of injury, which comprised the majority of our cases, are considered at more risk for soft tissue complications and arthrosis. 16,17 Based on frequent loss of fixation, persistent pain, and PTA, many surgeons have advocated for primary arthrodesis in a subset of Lisfranc injuries. 9,18 After ORIF, a high rate of unplanned secondary surgery was identified.…”
Section: Discussionmentioning
confidence: 99%
“…15 High-energy mechanisms of injury, which comprised the majority of our cases, are considered at more risk for soft tissue complications and arthrosis. 16,17…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting with clinical features suggestive of a midfoot sprain (localized midfoot pain, swelling and/or bruising) but with ≤2 mm gap between the medial cuneiform and the second metatarsal base on weight-bearing radiographs and/or CT/MRI imaging may be suitable for nonoperative treatment in appropriately selected patients 40,44 . Ponkilainen et al followed up 55 patients of an initial cohort of 110 who were treated initially in a non–weight-bearing cast for 4 to 6 weeks, followed by full weight-bearing for a further 4 weeks 45 . At a minimum follow-up of 2 years, patients reported excellent function according to the visual analog scale (VAS)-foot and ankle, and only 1 patient required delayed operative intervention.…”
Section: Treatmentmentioning
confidence: 99%